Enhanced solar light-driven photocatalytic degradation of pollutants and hydrogen evolution over exfoliated hexagonal WS2 platelets - Koyyada, G. (2019)
Two-dimensional (2D) layered structure transition metal dichalcogenides (TMDs) has been attracted huge attention and importance for photocatalytic energy conversion due to their unique properties. In this paper, exfoliated hexagonal WS2 (e-h-WS2) platelets were successfully synthesized by liquid-phase exfoliation (LPE) process from hexagonal WS2 (h-WS2) platelets in DMF solvent. The photocatalytic activity of e-h-WS2 and h-WS2 catalysts were compared systematically for degradation of various organic dye such as Congo red (CR), Methyl orange (MO), Phenol red (PR) and Rhodamine B (RhB)) pollutants and hydrogen production under simulated solar light irradiation. UV-vis and N2 absorption-desorption studies revealed that e-h-WS2 have shown narrow band gap and higher specific surface area than that of h-WS2. Enhanced photocatalytic activity was obtained for e-h-WS2 than h-WS2 i.e. 1.71 fold enhancement for hydrogen production rate. More importantly, this synthetic exfoliated procedure may open up an opportunity to synthesize other transition metal sulfides. Â© 2018 Elsevier Ltd